The Effects of Self-Acupressure on Pain, Fatigue, and Sleep Quality in Colon and Pancreatic Cancer Patients Receiving Chemotherapy - Bahcecioglu Turan, Gulcan; Ozer, Zulfunaz; Yanmis, Safiye; Aksoy, Asude (Lippincott Williams & Wilkins, 2023)
BackgroundPancreatic and colon cancer are among important gastrointestinal cancer diseases. Pain, fatigue, and insomnia are among the most common symptoms in cancer patients receiving chemotherapy. Self-acupressure may improve patients' pain, fatigue, sleep quality, quality of life, and functional well-being.ObjectiveThe aim of this study was to examine the effects of self-acupressure application on pain, fatigue, and sleep quality in colon and pancreatic cancer patients receiving chemotherapy.MethodsThis randomized controlled study was conducted with 60 patients in treatment for pancreatic or colon cancer, 30 in the intervention and 30 in the control group, between June and October 2021. Participants in the intervention group were asked to complete 16 acupressure sessions for 4 weeks, 2 days a week in the morning and afternoon for a total of 18 minutes, depending on the preparation and pressure time on 4 pressure points. Control group participants did not receive any interventions during the study. The data were collected by using a personal information form, the Pittsburgh Sleep Quality Index, the Piper Fatigue Scale, and the visual analog scale.ResultsAfter self-acupressure, the visual analog scale, Piper Fatigue Scale, and Pittsburgh Sleep Quality Index scores of the intervention group decreased when compared with the control group scores; the difference between the 2 groups was statistically significant.ConclusionSelf-acupressure was effective in reducing the pain, fatigue, and sleep disorder scores of patients with colon or pancreatic cancer receiving chemotherapy.Implications for PracticeIn nursing practice, self-acupressure, an applicable, accessible, and inexpensive method in the management of cancer-related symptoms, can be supported and maintained during a 4-week period.
Keywords: Colon cancer; Fatigue; Insomnia; Nurse; Pain; Pancreatic cancer; Self-acupressure